PENGARUH INTENSITAS KEBISINGAN AKTIVITAS PENERBANGAN TERHADAP TINGKAT KENYAMANAN MASYARAKAT DI SEKITAR BANDARA INTERNASIONAL SAM RATULANGI MANADO - Daffa Aulia Rizqi; Anton Budiarto; Laila Rochmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This research aims to ascertain whether the efforts made by the airport have fully met the standards in reducing the impact caused by flight activities at Sam Ratulangi International Airport, in accordance with Decree of the Director General of Highways No. 076/KPTS/Db/1999. This quantitative descriptive research method refers to the Decree of the Minister of Transportation No. KM 77 of 1998 concerning the Implementation of Public Airports and the Decree of the Director General of Highways No. 076 / KPTS / Db / 1999 regarding Guidelines for Noise Absorbing Building Engineering Planning. This type of research is descriptive research, data collection is done by means of observation and direct interviews using a questionnaire and the results of the measurement of noise intensity. The sample in this study were people living in the area closest to the airport, namely Teterusan, Wusa and Mapanget Barat villages, which were taken by simple random sampling.